Analysis of high frequency wave propagation characteristics in medium voltage XLPE cable model - Thayoob Y.H.M.; Ariffin A.M.; Sulaiman S. (2023)
Wave propagation characteristics of underground medium voltage cables are usually determined using the theory of natural modes of propagation. There are three important parameters involved in wave propagation along a cable which are the length of the cable, load condition, and propagation characteristics of the cable. Indeed, the last parameter is the most difficult one to be determined and normally should be modeled. Propagation losses occur in XLPE power cables as pulses propagate through the cable. Since different types of cable have different component parameters, the wave propagation characteristics such as attenuation and propagation speed will also vary accordingly. As such, the wave propagation characteristics for different cable types with their cable geometry are studied and analyzed using a developed MATLAB simulation model. 2010 IEEE.